Asymptomatic carriage of extensively drug-resistant bacteria (eXDR), a simple way to assess spontaneous clearance. Issue 4 (April 2020) - Farfour, E.; Si Larbi, A.-G.; Couturier, J.; Lecuru, M.; Decousser, J.-W.; Renvoise, A.; Faibis, F.; Lawrence, C.; Nerome, S.; Lecointe, D.; ,
Summary: The duration of eXDR carriage depends on several factors that might be difficult to recover. We aim to assess the duration of eXDR carriage by using a simple to recover parameter: the number of consecutive negative screening. 131 eXDR carriers (51 VRE and 80 CPE) were included. The number of consecutive negative screenings was strongly associated with eXDR clearance. All patients displaying at least three negative screenings over a seven-month period were never screened positive thereafter. Taking into account the number of negative screenings as a part of a case-by-case risk assessment would be helpful for the decision to maintain or lift eXDR-focused precautions.